Proenkephalin Derived Peptides Are Involved in the Modulation of Mitochondrial Respiratory Control During Epileptogenesis - Burtscher, Johannes; Bean, Camilla; Zangrandi, Luca; Kmiec, Iwona; Agostinho, Alexandra; Scorrano, Luca; Gnaiger, Erich; Schwarzer, Christoph (Frontiers in Molecular Neuroscience, 2018)
Epilepsies are a group of common neurological diseases exerting a strong burden on patients and society, often lacking clear etiology and effective therapeutical strategies. Early intervention during the development of epilepsy (epileptogenesis) is of great medical interest, though hampered by poorly characterized epileptogenetic processes. Using the intrahippocampal kainic acid mouse model of temporal lobe epilepsy, we investigated the functional role of the endogenous opioid enkephalin during epileptogenesis. We addressed 3 sequential questions: (1) How does enkephalin affect seizure threshold and how is it regulated during epileptogenesis? (2) Does enkephalin influence detrimental effects during epileptogenesis? (3) How is enkephalin linked to mitochondrial function during epileptogenesis? In contrast to other neuropeptides, the expression of enkephalin is not regulated in a seizure dependent manner. The pattern of regulation, and enkephalin’s proconvulsive effects suggested it as a potential driving force in epileptogenesis. Surprisingly, enkephalin deficiency aggravated progressive granule cell dispersion in kainic acid induced epileptogenesis. Based on reported beneficial effects of enkephalin on mitochondrial function in hypoxic/ischemic states, we hypothesized that enkephalin may be involved in the adaptation of mitochondrial respiration during epileptogenesis. Using high-resolution respirometry, we observed dynamic improvement of hippocampal mitochondrial respiration after kainic acid-injections in wild-type, but not in enkephalin-deficient mice. Thus, wild-type mice displayed higher efficiency in the use of mitochondrial capacity as compared to enkephalin-deficient mice. Our data demonstrate a Janus-headed role of enkephalin in epileptogenesis. In naive mice, enkephalin facilitates seizures, but in subsequent stages it contributes to neuronal survival through improved mitochondrial respiration.